Antimicrobial activities of irradiation-degraded chitosan fragments. (June 2019) - Zhang, Guojian; Li, Xiyang; Xu, Xiaofang; Tang, Ke; Vu, Viet Ha; Gao, Peng; Chen, Hao; Xiong, Youling L.; Sun, Qun
Abstract: Chitosan and its hydrolytic oligomers have been shown to exert antimicrobial effects in previous studies. The present study was conducted to explore the effect of γ-irradiation, which produces chitosan fragments, on the molecular weight (MW), solubility, and pH of degraded chitosan, and to investigate its underlying antimicrobial mechanism against bacteria and yeasts. The results showed that γ-irradiation at 100 kGy substantially decreased MW of chitosan with a degree of deacetylation (DD) of 90% from 435 kDa to 33 kDa. The solubility of chitosan fragments with a DD of 95% increased to 0.75 mg/ml from 0.02 mg/ml for intact chitosan, and the pH value rose from weakly acidic (6.81) to weakly alkaline (7.38) after irradiation at 200 kGy. In antimicrobial testing, the endoenzymes of microorganisms tested, i.e., Escherichia coli, Staphylococcus aureus, and Candida albicans, were found to leak out after treated with different MW chitosan fragments, with the 66 kDa component showing the greatest cell-disruption activity. Moreover, chitosan fragments at different MWs had varied lethal effects on Candida tropicalis, and the 66 kDa again produced a greater lethal effect than either 8 kDa or 197 kDa fragment. The 66 kDa fragment did not enter the cell of C. tropicalis as examined by laser confocal microscopy, suggesting that the inhibitory action targeted at cell surface rather than cell nuclei or other intracellular organelles. In conclusion, the γ-irradiation-induced 66 kDa deacetylated chitosan fragment with cell-lysing activity is a strong antimicrobial agent applicable in food systems to enhance safety and quality.